Stability of Adsorbent Sheets Under Accelerated-Aging Tests for Open-Cycle Adsorption Processes - Emanuela Mastronardo; Stefano De Antonellis; Angelo Freni; Candida Milone; Luigi Calabrese (Energies)
This study aims to assess the stability of silica gel/polymer composites designed for open-cycle air dehumidification, humidification, and heat storage by employing a comprehensive set of characterization methods. To evaluate their resistance to various environmental factors, the materials were subjected to a series of aging treatments: (i) repeated adsorption/desorption cycles under representative operational conditions; (ii) post-drying at 30 °C, 40 °C, and 60 °C; (iii) immersion in water for 30 days; (iv) exposure to a salt–fog environment for 30 days; and (v) accelerated aging by alternation between wet and dry cycles. Prolonged exposure to liquid water significantly reduced the material’s stability, resulting in an 83% reduction in tensile strength after 30 days of immersion. However, discontinuous exposure to liquid water at low drying temperatures did not critically affect the material’s mechanical properties during wet/dry cycles. Furthermore, post-drying (performed at 22 °C and 50% RH) allows the recovery of mechanical performance, with a tensile strength reached comparable to those of the unaged composites. Similarly, adsorption/desorption cycles in water vapor did not trigger degradation in the material, with its water vapor adsorption capacity remaining comparable to the unaged material after 100 cycles. The results confirm the reliability of these composite materials as to their potential uses in open-cycle dehumidification, humidification, and heat-storage applications.